Determinants and coverage of vaccination in children in western Kenya from a 2003 cross-sectional survey - Calhoun, Lisa M; van Eijk, Anna M; Lindblade, Kim A; Odhiambo, Frank O; Wilson, Mark L; Winterbauer, Elizabeth; Slutsker, Laurence; Hamel, Mary J (The American journal of tropical medicine and hygiene, 2014)
This study assesses full and timely vaccination coverage and factors associated with full vaccination in children ages 12-23 months in Gem, Nyanza Province, Kenya in 2003. A simple random sample of 1,769 households was selected, and guardians were invited to bring children under 5 years of age to participate in a survey. Full vaccination coverage was 31.1% among 244 children. Only 2.2% received all vaccinations in the target month for each vaccination. In multivariate logistic regression, children of mothers of higher parity (odds ratio [OR] = 0.27, 95% confidence interval [95% CI] = 0.13-0.65, P ≤ 0.01), children of mothers with lower maternal education (OR = 0.35, 95% CI = 0.13-0.97, P ≤ 0.05), or children in households with the spouse absent versus present (OR = 0.40, 95% CI = 0.17-0.91, P ≤ 0.05) were less likely to be fully vaccinated. These data serve as a baseline from which changes in vaccination coverage will be measured as interventions to improve vaccination timeliness are introduced.